ANALISIS DETERMINAN RETURN SAHAM YANG TERDAFTAR DI BEI PADA MASA TRANSISI COVID-19 - Sarah Inesya Anugrah Utami (2021)
This research is a quantitative study that aims to determine and analyze the effect of liquidity, company size, and interest rates on stock return in automotive companies and components listed on the Indonesia Stock Exchange in the period of Quarter IV 2020, Quarter I 2020, and Quarter II 2020. The population in this study were automotive and component companies that were listed and active on the Indonesia Stock Exchange during the fourth quarter of 2020, the first quarter of 2020, and the second quarter of 2020. This study used 12 companies as samples with the saturated sample method. The analysis technique used in this research is Panel Data Regression Analysis with the help of the E-Views version 10 program and a significance level of 5%. The results of this study indicate that (1) Liquidity (current ratio) has no significant effect on stock return of automotive and component companies, (2) Company size (total assets) has no significant effect on stock return, (3) Interest rates (BI 7-Days Repo Rate) has significant effect on stock return.